Palmoplantar hyperhidrosis: handicapped - Rasool, Anas (Journal of the Pakistan Medical Association, 2024)
Palmoplantar hyperhidrosis is a condition characterised by dysfunction of autonomic nervous system that results in overproduction of sweat from the palms and soles beyond physiological needs. It leads to social embarrassment and shattering of confidence having serious effects on quality of life1 Hyperhidrosis can be present at any age. The average age of onset for primary hyperhidrosis ranges from 14 to 25 years of age. The prevalence of Hyperhidrosis is higher among individuals 18 to 39 years of age than among adults > 65 years of age and children < 18 years of age2 Due to its embarrassing presentation and the general lack of knowledge about its medical nature, it is challenging to estimate the prevalence of Hyperhidrosis. In a developing country like Pakistan, people who don’t have this condition are not aware of the stress level of the patients suffering from hyperhidrosis. The quality of their professional work, social activities, taking part in games, personal relationships are highly compromised due to constant wetness of hands and feet which in some patients leads to anxiety, depression and social isolation3. The need of the hour is to find a treatment with a good success ratio. However, there are certain treatment options that are available but their results are not promising like antiperspirants consisting of aluminium chloride. If topical treatment fails, the patient can go for OnabotulinumtoxinA injection, units prescribed by the healthcare provider on sweaty areas (4). Another option is iontophoresis in which a mild bearable electric current is passed through your skin but its mechanism of action is not clearly understood5. some anticholinergic drugs like glycopyrrolate and oxybutynin can also be an option considering in mind that they will have a short list of side effects6. If nothing works, the last resort is sympathetic denervation7 The pressing priority is to find a permanent cure and create an awareness about this condition so that the affected people can come out of troubled waters and can live an anxiety free quality life. Continued...